Why More Leaflets? The Role of Natural Selection in Shaping the Spatial Pattern of Leaf-Shape Variation in Oxytropis diversifolia (Fabaceae) and Two Close Relatives - Wang, Hui; Liu, Pei-Liang; Li, Jian; Yang, Han; Li, Qin; Chang, Zhao-Yang (Frontiers in Plant Science, 2021)
Leaf shape exhibits tremendous diversity in angiosperms. It has long been argued that leaf shape can affect major physiological and ecological properties of plants and thus is likely to be adaptive, but the evolutionary evidence is still scarce. Oxytropis diversifolia (Fabaceae) is polymorphic for leaf shape (1 leaflet, 1-3 leaflets, 3 leaflets), and exhibits clinal variation in steppes of Nei Mongol, China. With two close relatives predominantly fixed for one phenotype as comparison (O. neimonggolica with 1 leaflet and O. leptophylla with 5-13 leaflets), we used a comprehensive cline-fitting approach to assess the role of natural selection in shaping the spatial pattern of leaf-shape variation in this system. For 551 individuals sampled from 22 populations, we quantified leaf morphological differentiation, evaluated patterns of neutral genetic variation using five chloroplast DNA intergenic regions and 11 nuclear microsatellite loci, and performed microhabitat and macroclimatic-association analyses. We found that 1-leaflet proportions in O. diversifolia populations significantly increased from west to east, and three phenotypes also differed in leaflet-blade size. However, compared with the other two species, populations of O. diversifolia showed little neutral genetic differentiation, and no population structure was detected at either marker. We further revealed that the leaf shape cline could largely be explained by three macroclimatic variables, with leaflet number decreasing and leaflet-blade size increasing with annual precipitation and showing the reverse trends with temperature seasonality and isothermality. Our results suggest that spatially varying abiotic environmental factors contributes to shape the leaf shape cline in O. diversifolia, while the interspecific pattern may be due to both local adaptation and historical events.